Fifty years of A‐level mathematics: have standards changed?. (18th February 2016) - Jones, Ian; Wheadon, Chris; Humphries, Sara; Inglis, Matthew
Abstract : Advanced‐level (A‐level) mathematics is a high‐profile qualification taken by many school leavers in England, Wales, Northern Ireland and around the world as preparation for university study. Concern has been expressed in these countries that standards in A‐level mathematics have declined over time, and that school leavers enter university or the workplace lacking the required mathematical knowledge and skills. The situation in England, Wales and Northern Ireland reflects more general international concerns about decreasing educational standards. However, evidence to support this concern has been of limited scope, rarely subjected to peer‐review and of questionable validity. Our study overcame the limitations of previous research into standards over time by applying a comparative judgement technique that enabled the direct comparison of mathematical performance across different examinations. Furthermore, unlike previous research, all examination questions were re‐typeset and candidate responses rewritten to reduce bias arising from surface cues. Using this technique, mathematics experts judged A‐level scripts from the 1960s, 1990s and the 2010s. We report that the experts believed current A‐level mathematics standards to have declined since the 1960s, although there was no evidence that they believed standards have declined since the 1990s. We contrast our findings with those from previous comparison studies and consider implications for future research into standards over time.